2021
DOI: 10.3390/cancers13246281
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Nationwide Infrastructure for Therapeutic Drug Monitoring of Targeted Oral Anticancer Drugs: The ON-TARGET Study Protocol

Abstract: Exposure-efficacy and/or exposure-toxicity relationships have been identified for up to 80% of oral anticancer drugs (OADs). Usually, OADs are administered at fixed doses despite their high interindividual pharmacokinetic variability resulting in large differences in drug exposure. Consequently, a substantial proportion of patients receive a suboptimal dose. Therapeutic Drug Monitoring (TDM), i.e., dosing based on measured drug concentrations, may be used to improve treatment outcomes. The prospective, multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Further complicating methotrexate dosing, the drug is 80% renally cleared, , and thus, reductions in kidney function arising due to disease or to methotrexate toxicity can further increase drug exposure. Given these mechanisms, using laboratory-based therapeutic monitoring to ensure that methotrexate exposure remains within the acceptable risk/benefit window and to identify when countermeasures should be employed has already proven of significant clinical value , despite its limited time resolution (typically one measurement per day). ,, Although human clinical trials will be required, obviously, in order to confirm this, we believe that it is a reasonable assumption that the high-resolution, real-time information EAB sensor could substantially improve on this current standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating methotrexate dosing, the drug is 80% renally cleared, , and thus, reductions in kidney function arising due to disease or to methotrexate toxicity can further increase drug exposure. Given these mechanisms, using laboratory-based therapeutic monitoring to ensure that methotrexate exposure remains within the acceptable risk/benefit window and to identify when countermeasures should be employed has already proven of significant clinical value , despite its limited time resolution (typically one measurement per day). ,, Although human clinical trials will be required, obviously, in order to confirm this, we believe that it is a reasonable assumption that the high-resolution, real-time information EAB sensor could substantially improve on this current standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…As there is a clear relationship between 5FU exposure and response, accounting for this variability is a crucial task which can only be satisfactorily solved in conjunction with TDM. The topic of precision dosing in oncology is gaining more attention in the recent years as an emerging number of studies has assessed the benefits of TDM, especially for oral anticancer drugs [4,142,[203][204][205][206]. Furthermore, it was shown that pharmacometric modeling approaches have a great potential to significantly contribute towards precision dosing of 5FU.…”
Section: Therapeutic Drug Monitoring Of Fluorouracilmentioning
confidence: 99%
“…The changes in the treatment of malignancies brought about by OACDs have been revolutionary, considering their favorable adverse effect profiles and applicability as a regular pill medication. Indeed, targeted therapies with OACDs offer significant benefits to patients, clinicians, and the healthcare system with reduced treatment costs, milder and more tolerable adverse effects, and improved prognoses [ 1 ]. The range of malignancies that have been treated successfully keeps increasing, with regulatory agencies having granted approvals to over 80 OACDs for treating various types of cancers including central nervous system (CNS) tumors, hematological malignancies, gastrointestinal tumors, and melanoma, as well as non-small cell lung carcinoma (NSCLC), since 2001 [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the remarkable inter-individual variability in their pharmacokinetic properties raises the need for the individualization of OACD regimens based on the monitoring of drug exposure [ 3 ]. Therapy adherence also influences the outcome of the treatment [ 1 ]. An increasing number of publications suggests that therapeutic drug monitoring (TDM), as well as the pharmacokinetic interpretation of TDM results, have key importance in optimizing targeted oncotherapy using OACDs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%